STUNTING PREVENTION PROGRAM IN NORTH BENGKULU REGENCY - Linda Safitra; Fitria Yuliani; Abdul Tofandi (Jurnal Ilmu Sosial Mamangan, 2021)
This study aims to analyze the stunting prevention program in North Bengkulu Regency through the AGIL concept proposed by Talcot Parsons in the theory of Structural Functionalism. This study uses a qualitative research approach, with case studies. The type of research used is a more in-depth descriptive. Research data were collected through observation techniques, unstructured interviews and document collection. Research informants were determined through purposive sampling technique. The results showed that there were 4 stunting prevention programs in North Bengkulu Regency, namely maternal and child health service programs, nutrition counseling programs and supplementary feeding, social protection programs and sanitation and clean water programs through the use of village funds. These four programs were able to reduce stunting rates in the research locations. Implementation of the program is emphasized on the process of community empowerment. The main targets are changes in personal health behavior and environmental health behavior. The process of adaptation, goal setting, integration, and pattern maintenance are also fairly well systemized in the program realization process. In the future, program implementation needs to be accompanied by the economic maturity of the community.